Reflections on Sociology of Law in Law Enforcement in society - Hartanto (PT FORMOSA CENDEKIA GLOBAL, 2023)
Sociology cannot be used directly in the context of distorting the scope of legal science in its independent substance, legal sociology is a middle way with its various slices. The complex reality in society provides many distortions as to whether law can be independent or a truly substantially open system, in the midst of our legal development position which was previously the perspective of Dutch scientists and is currently required to accommodate